PENINGKATAN LITERASI DIGITAL SISWA MELALUI MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL KASEPUHAN PADA PEMBELAJARAN PPKn - Uyandi, Uyandi; Luthfi Hamdani Maula; Din Azwar Uswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aimed to improve digital literacy among fourth-grade students through local-wisdom-based learning media at SDN Linggarjati, a remote school in the Kasepuhan Ciptarasa indigenous community, Cikakak, Sukabumi. The school faces limited electricity (3 p.m.–9 a.m. only) and no internet access. The study involved eight students using the Kemmis and McTaggart spiral model across two cycles. Learning media consisted of a battery-powered laptop loaded with offline digital content—photographs and documentary videos of the Seren Taun ceremony, communal cooperation activities, and local arts—integrated into Civics (PPKn) lessons on cultural diversity and indigenous identity. Data were collected through observation sheets, self-assessment digital literacy questionnaires, interviews, and reflective journals. Results showed that the average digital literacy score increased from 17.00 (30.36%) in the pre-cycle to 21.50 (38.39%) after Cycle I, and rose sharply to 40.88 (73.00%) after Cycle II. By the end of Cycle II, four of eight students reached the Proficient level and the remaining four reached the Developing level, all having started at the Emerging level. The findings indicate that local-wisdom-based offline digital learning media effectively improves the technical, cognitive, and socio-emotional dimensions of digital literacy even under severe infrastructural constraints, while simultaneously strengthening students' appreciation of their local cultural identity.